Management of anterior submandibular sialolithiasis - Duong Lucas T.; Kakiche Thomas; Ferré François; Nawrocki Laurent; Bouattour Ayman (EDP Sciences, 2019)
Introduction: Sialolithiasis is defined by the presence of a calculus within the salivary gland or its excretory system. It primarily affects the submandibular gland at a frequency of 80%. Involving many factors, the exact aetiology and pathogenesis of salivary calculi remain to be discussed. Body: The purpose of this article is to expose the different aspects of the pathology. Aetiological factors, the diagnostic approach which requires the use of imaging tests as well as the medical and surgical management of anterior submandibular sialolithiasis, will be described. A decision tree regarding the type of management and a table summarizing the main differential diagnoses will be proposed. Conclusion: Submandibular sialolithiases are a common salivary gland disorder. The treatment of sialolithiasis must be early and remains mainly surgical. The level of cooperation as well as the patient's medical and surgical history should guide the management of this type of disorder of the salivary system.